Evaluating SMEs Readiness to Transform to IoT-Based Business Models - Elena Vitkauskaitė; Viktorija Varaniūtė; Harry Bouwman (International Telecommunications Society (ITS), 2019)
The connection of devices, as enabled by the Internet of Things (IoT), has a significant impact on business activities, processes, and performance. IoT is, therefore, gaining attention from practitioners and academia. The deployment of technological innovations is inseparable from changes in business activities, and therefore also affects business models (BMs) of both large corporations as well as small and medium-sized enterprises (SMEs). Both face challenges on transformations to their business models due to the use of IoT solutions, although these changes might be different for both. Extant literature on IoT-based business models mainly focuses on transformations in large companies. Since SMEs play an important role in the market's value creation, it is particularly important to understand SMEs business model transformations, caused by IoT. Research on this topic is limited and faces many theoretical and methodological challenges. Therefore, this paper proposes a mixed method approach to study SMEs readiness to transform business models as a result of implementing IoT solutions. Based on a systematic literature review, and a pilot study (by using a case of one SME in Lithuania), we developed a mixed method research design in which input-output relation between case studies for theory formulation as well as theory testing are proposed.
Keywords: 330; Internet of Things; Business Model; IoT; SME; mixed-method research